Does improvement of environmental information transparency boost firms' green innovation? Evidence from the air quality monitoring and disclosure program in China. (10th July 2022) - Zhang, Sihan; Zhang, Ming-ang; Qiao, Yuanbo; Li, Xiao; Li, Sheng
Abstract: Transparent environmental information is fundamental for the government to better regulate pollution and for the public to be aware of pollution. However, how the improvement of environmental information transparency affects firms' environmental behavior has been underexplored. This paper fills this gap by exploring the impact of China's air quality monitoring and disclosure program on the green innovation of firms; via this program, real-time air quality monitoring stations have been constructed nationwide, and the information is promptly released to the public. The results of a difference-in-differences estimation show that the information program has significantly increased the green innovation of firms, especially the number of green invention patent applications. Moreover, this increase is realized via the regulatory effect of both the local government and public attention. Additionally, the green innovation effect performs stronger in state-owned enterprises (SOEs) and firms in heavily polluting industries. This paper contributes to the related literature from the perspective of central government-led real-time transparent environmental information disclosure. The findings of this study highlight policy implications from the perspective of the importance of the application of information technology in environmental regulation, as well as the vital role of information-based instruments in exerting a public regulatory effect on environmental governance. Highlights: Effect of pollution information disclosure on firm's green innovation is tested. DID is used exploiting China's Air Quality Monitoring-and-Disclosure Program. The pollution information disclosure significantly boosts firm' s green innovation. The mechanism is the regulatory effect from local governments and public attention. Porter's Hypothesis is supported from the new view of information disclosure.